Revitalisasi Karya Sastra Islami dalam Pembelajaran Bahasa Indonesia untuk Membangun Karakter Islami MA Darul Ulum II Bujur Tengah Pamekasan - Wafi, Abdul; Hasan, Moh. Khalid (Lembaga Intelektual Muda (LIM) Maluku, 2024)
This study aims to explore and analyze the revitalization of Islamic literary works in Indonesian language learning at MA Darul Ulum II Bujur Tengah Pamekasan, focusing on three main aspects: the use of Islamic literary works in learning, the teaching methods applied by teachers, and their impact on the formation of students' Islamic character. Through a qualitative approach, data is collected through observation, interviews with teachers and students, and analysis of learning documents. Data analysis techniques consist of data reduction, data presentation, and conclusion drawn. The results of the study show that the use of Islamic literary works has been carried out significantly, with the selection of relevant works to support learning objectives and Islamic values. The teaching methods used by teachers include interactive discussions, critical readings, and creative activities that actively engage students, thereby increasing their engagement and understanding of the material. In addition, the impact of teaching Islamic literary works on students' character can be seen from the improvement of Islamic attitudes, behaviors, and values applied in daily life. This study concludes that the revitalization of Islamic literary works in Indonesian learning not only enriches students' learning experience, but also contributes to the development of strong Islamic characters.